Literature review of security issues in saas for public cloud computing: a meta-analysis - Shakir, Mohanaad; Hammood, Maytham; Kh. Muttar, Ahmed (International Journal of Engineering and Technology, 2018)
Cloud computing is a rapidly growing technology due to its highly flexible uses and applications. It also has other features such as simplicity, quick data access and reduced data storage costs. Consequently, it has been widely used by many organizations. This widespread use of cloud computing among organizations causes many security issues. Moreover, cloud computing layers are likely to be jeopardized by many security risks such as privileged user access, data location, data segregation, and data recovery. This paper aims to prepare an ample debate of a literature review-based studies that provided important insights to researchers in the scope of security cloud computing. The researcher applied a relevant set of keywords. These keywords are limited to the title, abstract and keywords search archives published between 2010 and June 2017. The database search returned a total of 308 publications. In addition, we conducted backward-forward searches from the reference lists of relevant, quality previous works on the security framework in public cloud computing studies. Then, the researcher filtered the publications to only full text access articles that were written in English only. Finally, this study obtained a total of 53 publications. The findings of this paper address many important points such as authentication, data segregation, and encryption which are considered as the top concerns in security cloud computing. In addition, most of authentication layer is considered password as a prime criterion in determining authorizes user.Â Â